Origin and perspectives of Intercultural Bilingual Education policies in Peru: utopia towards a quality IBE - Ruelas Vargas, David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: of the research is to contribute to the study of the origin and perspectives of Intercultural Bilingual Education policies in Peru, which seeks to serve native peoples as a compensatory pedagogical measure for the implementation in schools of Castilianization, which caused difficulties in the learning of children from indigenous peoples. In Peru, a multiethnic, multicultural and multilingual country where various Andean, Amazonian and coastal peoples coexist, the Ministry of Education of Peru recognizes the existence of 43 native languages ​​in the Amazon and 4 in the Andes. Originality/support: consists of addressing and analyzing the development and implementation of IBE policies in the Peruvian educational system. Method: applied is historical and was supported with the library technique and analysis and interpretation of historical documents from primary and secondary sources, the information collection Strategy/ information gathering: was based on the analysis of texts, articles, archives and magazines. Conclusions: bilingual education policies of the 20th and 21st centuries have been mediated by globalization and transnational organizations such as the International Monetary Fund, World Bank, Inter-American Development Bank - Washington, indigenous peoples are not free from their influence. Due to the ethnolinguistic and multicultural diversity in Peruvian education in the 21st century, languages ​​are a priority as a valid means of learning because they possess knowledge and knowledge. Quality bilingual education for indigenous peoples remains a utopia.